Catchment Delineation and LULC Classification of the Upper Catchment of the Timah-Tasoh Reservoir Using DEM and GIS - Nordin, Nor Aisyah Syafiqah; Hassan, Zulkarnain; Mohamed Noor, Norazian; Kamarudzaman, Ain Nihla; Ag Ahmadni, Ag Shaffie (International Journal of Integrated Engineering, 2025)
The catchment plays a crucial role in delineating basin boundaries and creating sub-basins within it. By using Geographic Information System (GIS), it becomes capable of identifying the sub-catchments within the Timah-Tasoh reservoir. GIS has evolved into an indispensable tool for mapping and evaluating ecosystems in given area. By employing various parameters, significant hydrological processes can be identified and quantified in both small and large catchment areas. This study aims to determine the hydrological characteristics of the reservoir’s sub-catchments. The catchment is delineated using the Digital Elevation Model (DEM), and this analysis is performed through ArcGIS. The result indicates that ArcGIS 10.7.1 can determine the catchment delineation and land use classification for the Timah-Tasoh reservoir. Following the delineation procedure, 19 sub-catchments covering a total area of 183.34 km2 were identified, and the land cover was reclassified into five categories; agriculture, built-up areas, forest, vacant land and water bodies. Therefore, considering the possibility of utilizing ArcGIS for future expansion of this study can enhance the understanding.